Pengaruh Modal Kerja Terhadap Penjualan dan Laba Bersih Pada Perusahaan Sub Sektor Food and Beverages Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Atin Ari Mawar Astuti; andria referli; milka susana (Universitas Boyolali, 2020)
In the activities of a company, the main problem is working capital. Working capital is the capital used to run a company’s operations. Because without sufficient working capital, the company will experience a financial crisis and the most worrying is bankruptcy. This research aims to knowing the effect of working capital on sales and net income in the Food and Beverages sub-sector companies listed on Indonesia Stock Exchange 2013-2017. The type of data used is secondary data, that is about financial statements. Sampling technique used purposive sampling as much 12 company’s. All data analyzed with classic assumption test, simple linear regression analysis, t test, determination coefficient. Research result indicate with significant level 0.05 that working capital has a positive effect on sales and net income. Keyword : Working Capital, Sales, Net Income